Readiness Analysis of ISO 9001: 2015 Quality Management System Implementation Using Gap Analysis Method - Khairul Anshar; Bakhtiar; Fara Anjelika; Amri; Fatimah (Jurnal Informasi dan Teknologi, 2025)
PT Pelindo Multi Terminal is a subsidiary of PT Pelabuhan Indonesia (Persero), which manages port services business in the field of multipurpose terminal operations in Indonesia. which was inaugurated on October 1st, 2021, resulting in a merger between PELINDO I, II, III, and IV. Until now, PT Pelindo Multi Terminal is still following PELINDO 1 regulations, one of which is the implementation of ISO 9001: 2008, which ISO 9001: 2008 has expired in September 2020. Therefore, PT Pelindo Multi Terminal must adjust the Quality Management System (QMS) to the latest version of the standard, namely QMS ISO 9001: 2015, and apply for ISO 9001: 2015 certification in order to maintain the quality of its service. The purpose of this study was to determine the readiness and constraints in implementing and obtaining ISO 9001: 2015 QMS certification. The method used in this research is Gap Analysis. Gap Analysis is a measurement method to determine the gap by mapping the current QMS and comparing it with the ISO 9001: 2015 QMS requirements, to obtain an analysis of the differences between the current QMS at PT Pelindo Multi Terminal and the ISO 9001: 2015 requirements. From the gap analysis results, PT Pelindo Multi Terminal has a readiness level of 88% to complete the ISO 9001:2015 QMS requirements and is ready to convert its QMS from ISO 9001:2008. However, based on the overall research results, there are still requirements, and some work procedures have not been carried out consistently. This is due to the lack of socialization and training on the implementation of ISO 9001:2015 after the merger, and the limited time and lack of human resources in checking internal audits to determine the suitability of SOPs that have been made.